Dual pH/redox responsive and CD44 receptor targeting hybrid nano-chrysalis based on new oligosaccharides of hyaluronan conjugates. (10th February 2017) - Chen, Daquan; Dong, Xue; Qi, Mengjiao; Song, Xiaoyan; Sun, Jingfang
Highlights: We designed a dual pH/redox responsive menthone ketal (oHSMC) based oligosaccharides of hyaluronan (oHA) conjugate. We developed a novel loaded curcumin (Cur) nano-chrysalis inspired by butterfly pupa with oHSMC and inorganic CaP. The nano-chrysalis has an inner core composed of specially designed oHA targeting CD44 receptor. The nano-chrysalis could release encapsulated curcumin with accelerated rate under lower pH and redox condition. The nano-chrysalis was less toxic and suppressed tumor growth most efficiently. Abstract: A smart hybrid microenvironment-mediated dual pH/redox-responsive polymeric nanoparticles combined with inorganic calcium phosphate (CaP) was fabricated, which we term as armored nano-chrysalis inspired by butterfly pupa. The nano-chrysalis has an inner core composed of specially designed oligosaccharides of hyaluronan (oHA) targeting CD44 receptor. The inner core has two functions, i.e., the dual pH/redox responsive polymeric conjugate and the fluorescent curcumin-prodrug function. The prepared nano-chrysalis possessed a smaller size (102.5 ± 4.6 nm) than the unarmored nano-chrysalis (122.5 ± 6.6 nm). Interestingly, while the nano-chrysalis were stable under pH 7.4, when incubated under the tumor acidic conditions (pH 6.5) the outer CaP armor would dissolve in a pH-dependent, sustained manner. Moreover, nano-chrysalis was demonstrated to present the most effective antitumor efficacy than other formulations. This study provides a promising smart nano-carrier platform to enhance the stability, decrease the side effects, and improve the therapeutic efficacy of anticancer drugs.